Tet1 and Tet2 protect DNA methylation canyons against hypermethylation - Wiehle, Laura; Lyko, Frank; Breiling, Achim (Molecular and cellular biology, 2016)
DNA methylation is a dynamic epigenetic modification with an important role in cell fate specification and reprogramming. The Ten eleven translocation (Tet) family of enzymes converts 5-methylcytosine to 5-hydroxymethylcytosine, which promotes passive DNA demethylation and functions as an intermediate in an active DNA demethylation process. Tet1/Tet2 double-knockout mice are characterized by developmental defects and epigenetic instability, suggesting a requirement for Tet-mediated DNA demethylation for the proper regulation of gene expression during differentiation. Here, we used whole-genome bisulfite and transcriptome sequencing to characterize the underlying mechanisms. Our results uncover the hypermethylation of DNA methylation canyons as the genomic key feature of Tet1/Tet2 double-knockout mouse embryonic fibroblasts. Canyon hypermethylation coincided with disturbed regulation of associated genes, suggesting a mechanistic explanation for the observed Tet-dependent differentiation defects. Based on these results, we propose an important regulatory role of Tet-dependent DNA demethylation for the maintenance of DNA methylation canyons, which prevents invasive DNA methylation and allows functional regulation of canyon-associated genes.
Gesehen am 19.08.2020